An Investigation into the Interrelation of the First and the Foreign Languages Reading Comprehension Proficiencies: Linguistic Interdependence Versus Balance Hypotheses - Pirooz, Hasan; Khaghaninejad, Mohammad Saber (Jordan Journal of Modern Languages & Literatures, 2023)
This research investigated the efficiency of either the Linguistic Interdependence Hypothesis (LIH) or the Balance Hypothesis (BH) for the possible association of the first and the foreign reading comprehension proficiencies for EFL learners. The impact of the participants’ “age” and “gender” were also assessed for this interrelation. Hence, a total of 52 Persian monolinguals and 156 bilinguals (Iranian learners of English, Arabic and French) were selected randomly and recruited for the study. The needed data were obtained via four validated reading comprehension tests of GMAT, TOEFL, DELF, and ALPT as the research instruments. Statistical analyses revealed a strong positive connection between the learners’ first and second languages reading comprehension as a support for LIH which implies the existence of a general reading comprehension competence involved in reading comprehension tasks of different languages. No statistically significant effects were found for the roles of “gender” and “age” in L1 and L2 reading competence interconnection.